Unlocking Profitability: Exploring Green Production Adoption and Financial Performance in Malaysian SME Manufacturing - Krishnan, Vijayaletchumy; Jayabalan, Neeta; Prebakarran, Praveena Nair; T. Pentang, Jupeth; Zedan, Liu (Journal of Ecohumanism, 2024)
The adoption of green practices in Small and Medium Enterprises (SMEs) has gained significant traction as organizations strive to balance economic growth with environmental sustainability. This study provides a comprehensive review of recent research on green practices and their impact on organizational performance, particularly within the context of SMEs in Malaysia and other regions. By examining a range of studies, including empirical analyses and theoretical explorations, this review identifies key drivers, challenges, and outcomes associated with the implementation of green practices. Factors such as competitive pressures, regulatory influences, and green innovation are highlighted as critical elements influencing the adoption of sustainable practices. The findings underscore the role of green practices in enhancing operational efficiency, reducing environmental impact, and improving financial performance. This study contributes to a deeper understanding of how SMEs can strategically integrate green practices to achieve sustainable development goals and offers practical insights for policymakers and business leaders aiming to foster environmental responsibility in the SME sector.